The Extensive Margin of Aggregate Consumption Demand - Michelacci, Claudio; Paciello, Luigi; Pozzi, Andrea (Review of Economic Studies, 2022)
Abstract About half of the change in U.S. non-durable consumption expenditure is due to changes in the products entering households’ consumption basket (the extensive margin). Changes in the basket are driven by fluctuations in the rate at which households add products; removals fluctuate little. These patterns reflect that, in response to income increases, households adopt consumer products already available in the market. Household adoption amplifies the effects of fiscal transfers on consumption by more than 30%. Cyclical household adoption of products also implies that inflation measures based on a representative household consuming all varieties available in the market underestimate true household-level inflation by as much as 1% per year over the Great Recession in the consumption categories covered by our data.